The Effect of Foot Massage on Comfort and Pain Intensity After Vaginal Delivery - Nikmah Jalila Ritonga; Anuhgera, Diah Evawanna; Damayanti (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Childbirth is a mother's subjective experience that is very memorable in her life. It is important to maintain maternal comfort so that the process of adapting to motherhood can run well. Pain during postpartum is one of the factors that prevents mothers from having difficulty adapting during the postpartum period, especially in primapara mothers. A pharmacological method that can be given to increase comfort and reduce the intensity of pain is foot massage. The aim of this study was to determine the effect of foot massage on the comfort and intensity of maternal pain after vaginal delivery during the postpartum period. This type of quasi-experimental research sample consisted of 38 respondents and the sampling technique used simple random sampling. This research was conducted at the Independent Early Midwife Practice in Lubuk Pakam. Respondents consisted of 2 groups, namely the intervention group and the control group. The instruments used were questionnaires, Visual Analog Scale (VAS), Post Partum Comfort Scale (PCS). Data analysis used chi-square/Fisher's exact test, independent-samples t test and one-way analysis of variance (ANOVA). The mean maternal comfort score in the intervention group was higher than the control group (143.45 ± 8.96, 119.00 ± 14.65, respectively) with a value of p = 0.000. The mean pain score in the intervention group was lower than the control group (1.36 ± 1.22, 4.95 ± 2.27) and the p value = 0.000. Foot massage is effective in increasing comfort and reducing the intensity of pain after vaginal delivery. The increase in maternal comfort after intervention was 18.34% and the reduction in pain intensity after vaginal delivery was 73%. In this way, midwives can apply foot massage to every mother after vaginal delivery.